2019
DOI: 10.15171/jlms.2019.s16
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Proteomic Investigations on the Development and Improvement of Skin Laser Therapy: A Review Article

Abstract: Introduction: Different molecular approaches have contributed to finding various responses of skin to external and internal tensions such as laser irradiation and many important mediators of skin disease have been identified through these approaches. However, different essential signals of skin biomarker pathways and proteins are partially detected or completely unknown. In the present study, the impact of proteomics on the evaluation of laser therapy for the treatment of skin diseases is investigated. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Proteomics has less technical limitations on protein identification and a large number of proteins could be identified by this technique. 71 Proteomic analysis of foot skin compared to breast skin demonstrated the presence of 50 ECM common proteins in both skins, but there was a difference between the expressions of tenascin-x in breast skin and serum amyloid p component in foot skin. 72 By examining the proteomic profile of elderly epidermis, it was found that interferonstimulating polypeptides expression increased, causing the stimulation of phosphatidylinositol 3-kinase and manganese superoxide dismutase.…”
Section: Molecular Aspects Of Laser Effects In Cell Biologymentioning
confidence: 96%
“…Proteomics has less technical limitations on protein identification and a large number of proteins could be identified by this technique. 71 Proteomic analysis of foot skin compared to breast skin demonstrated the presence of 50 ECM common proteins in both skins, but there was a difference between the expressions of tenascin-x in breast skin and serum amyloid p component in foot skin. 72 By examining the proteomic profile of elderly epidermis, it was found that interferonstimulating polypeptides expression increased, causing the stimulation of phosphatidylinositol 3-kinase and manganese superoxide dismutase.…”
Section: Molecular Aspects Of Laser Effects In Cell Biologymentioning
confidence: 96%
“…In these fields, the laser stimulates or inhibits cell and tissue function which leads to clinical effects finally. [17][18][19][20] Before laser therapy, patients' history including abnormal scarring, allergy, excessive sun exposure, herpes virus infection, any vascular and immunological disorders, tissue reinforced with silicone, smoking, and former cosmetic surgery must be considered. Because many drugs including amiodarone, minocycline, warfarin, isotretinoin, aspirin, niacin, vitamin E cause delayed healing, bleeding, scarring, increased bruising, hyperpigmentation, and localized chrysiasis after laser therapy, the medications that the patients have taken must be considered.…”
Section: Epidermal Side Effects Of Laser Therapymentioning
confidence: 99%
“…The second group of genes (the DEGs that existed in the control and light-damage analysis but were absent in the PBM and PBM+light-damage analysis) was selected to screen via PPI network analysis by using Cytoscape software. 13 The genes were imported in Cytoscape and included in a network via the "protein query" of the STRING database. Due to poor interaction between the query genes, the 20 first neighbors of the nodes were added to the DEGs from the STRING database.…”
Section: Gse22818mentioning
confidence: 99%